(untitled) (Research, Society and Development, 2024)
This study aimed to investigate the challenges of physiotherapeutic work with elderly people in Home Care through the Family Health Strategy in the SUS, through an integrative literature review. The data sources used were electronic databases and searches in the reference list of articles. The articles were searched in the electronic databases: VHL, Scielo, PubMed, Lilacs and PEDro, using the search strategies for combinations of the following descriptors selected from the Health Sciences Descriptors (DECS) database: Physiotherapy, Elderly, Home care, Health of the family and the Unified Health System. The objective of the article search was to include scientific publications that addressed the objective of the research, with full text available, covering at least one of the chosen descriptors, published from 2018 to 2023, in Portuguese, English and/or Spanish. After applying the criteria and reading the findings, 8 articles were selected to compose the review. It was observed that the performance of home physiotherapy for the elderly in the Family Health Strategy (ESF) can be of great importance, presenting a range of possibilities for conduct, protocols and parameters. It was found that in this context a series of complex challenges are faced. To advance the understanding of these challenges, research is needed that integrates varied methodologies, such a longitudinal studies that track the impact of interventions over time, qualitative analyzes to understand the perspectives of the elderly, caregivers and health professionals involved, and case studies that identify good practices and challenges faced in specific contexts.